Respuesta :
Answer:
Explanation:
Given
[tex]F(x)=x^3[/tex]
Rate of change of F(x) is given by
[tex]F'(x)=\lim_{h\rightarrow 0}\\\frac{F(x+h)-F(x)}{x+h-x}[/tex]
[tex]F'(x)=\lim_{h\rightarrow 0}\\\frac{(x+h)^3-x^3}{h}[/tex]
[tex]F'(x)=\lim_{h\rightarrow 0}\\\frac{x^3+h^3+3x^2h+3xh^2-x^3}{h}[/tex]
[tex]F'(x)=\lim_{h\rightarrow 0}\\\frac{h^3+3x^2h+3xh^2}{h}[/tex]
[tex]F'(x)=\lim_{h\rightarrow 0}\\h^2+3x^2+3xh[/tex]
Putting limits
[tex]F'(x)=3x^2[/tex]
The average rate of change will be "3x²".
Average rate of change
According to the question,
The function, f(x) = x³
then,
f(x + h) = (x + h)³
Now,
→ f(x + h) - f(x) = (x + h)³ - x³
= x³ + h³ + 3x²h + 3xh² - x³
= h³ + 3x²h + 3xh²
and,
→ [tex]\frac{f(x+h) -f(x)}{h}[/tex] = [tex]\frac{h^3+3x^2h+3xh^2}{h}[/tex]
= [tex]\frac{h[h^2+3x^2+3xh]}{h}[/tex]
= h² + 3x² + 3xh
By applying the limit, we get
→ [tex]\lim_{h \to 0} \frac{f(x+h)-f(x)}{h}[/tex] = [tex]\lim_{h \to 0}[/tex] h² + 3x² + 3xh
By substituting the values,
= 0² + 3x² + 3x(0)
= 3x²
Thus the above approach is correct.
Find out more information about Average rate here:
https://brainly.com/question/8728504